(untitled) (Third Sector Social Economic Review, 2023)
The evolution of information and communication technologies has affected every sector and brought significant innovations to the banking sector. In the process of digitization of the Turkish Banking Sector, the services offered by banks to their clients have diversified following the evolution of internet technologies. The purpose of this study was to examine the effects of digital banking services such as internet banking and mobile banking on bank performance. The data used in the research were collected from the website of the Association of Turkish Banks, including the period 2011-2022. In the analysis of the data, a multiple linear regression analysis method was utilized. As a result of the research, digital banking has been found to have an important and positive impact on bank performance. In addition, the effect of the average transaction volume made with mobile banking services on the bank performance is higher than the effect of the average transaction volume made with internet banking services.